The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/mc.22740
|View full text |Cite
|
Sign up to set email alerts
|

TNFAIP8 regulates Hippo pathway through interacting with LATS1 to promote cell proliferation and invasion in lung cancer

Abstract: TNFAIP8 is associated with prognosis of several human malignancies. However, the molecular mechanism of TNFAIP8 in lung cancer remains unknown. In our study, we found TNFAIP8 could enhance TEAD luciferase activity and inhibits the activity of Hippo pathway. TNFAIP8 also increased cyclin D1, CDK6, and decreased p27 in lung cancer cells. In addition, TNFAIP8 increased total YAP protein and promoted nuclear localization of YAP. More importantly, YAP depletion blocked the role of TNFAIP8 on cell cycle-related prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…Overexpression of YAP in EOC cells efficiently attenuated cell growth inhibition in TNFAIP8-deficient EOC cells. These data are consistent with those of previous studies that demonstrated the regulatory role of TNFAIP8 in Hippo signaling ( 28 , 29 ). Additional experimental studies also suggest the involvement of TNFAIP8 in apoptosis and cell cycle checkpoint protein expression in EOC cells, which were identified as downstream targets of YAP ( 7 , 8 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Overexpression of YAP in EOC cells efficiently attenuated cell growth inhibition in TNFAIP8-deficient EOC cells. These data are consistent with those of previous studies that demonstrated the regulatory role of TNFAIP8 in Hippo signaling ( 28 , 29 ). Additional experimental studies also suggest the involvement of TNFAIP8 in apoptosis and cell cycle checkpoint protein expression in EOC cells, which were identified as downstream targets of YAP ( 7 , 8 ).…”
Section: Discussionsupporting
confidence: 93%
“…Dai et al ( 26 ) demonstrated that TNFAIP8 upregulated cell proliferation, migration, invasion, and xenograft tumor growth in HCC cells. TNFAIP8 also promoted cell proliferation and invasion in lung cancer ( 29 ). Concurrently, downregulated expression of TNFAIP8 via the overexpression of microRNA (miR)-9 markedly inhibited gastric cancer cell proliferation in vitro and tumor growth in vivo ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The gene is located on chromosome 5q23.1 and is expressed in most malignant foot tumor tissues. Studies on these tumors have all suggested that signal transduction pathway affects many processes such as cell apoptosis, and therefore plays an important role in the formation and development of tumors [8]. In recent years, a series of functions of TNFAIP 8 in tumor formation have been continuously con rmed.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of transcriptional coactivator and a Hippo pathway effector YAP1 has been associated with resistance to TKI and BRAF inhibitors, upregulation of PD-L1, and poor survival in NSCLC (23,24). TNFAIP8 has been shown to interact with LATS1, one of the Hippo core components, and promote nuclear localization of YAP and expression of downstream targets cyclin D1 and CDK6 in lung cancer cells (25).…”
Section: Introductionmentioning
confidence: 99%